2018
DOI: 10.1101/330753
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Construction of high-density genetic maps and detection of QTLs associated with Huanglongbing infection in citrus

Abstract: No true resistance to Huanglongbing (HLB), a citrus disease associated with infection of Candidatus Liberibacter asiaticus (CLas), is found within commercial citrus cultivars, though trifoliate orange (Poncirus trifoliata) has been described as resistant or tolerant. Through genotyping an intergeneric F1 population by Genotyping-by-Sequencing, high-density SNP-based genetic maps were constructed separately for trifoliate orange and sweet orange (Citrus sinensis). Both genetic maps exhibited high synteny and hi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
(89 reference statements)
1
2
0
Order By: Relevance
“…In addition, many other genotypes used as pollen donors were incompatible with the maternal plant. Despite these limitations, this is a high density map which is consistent with data collected by other authors using similar models and techniques (Worthington et al, 2016, Huang et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, many other genotypes used as pollen donors were incompatible with the maternal plant. Despite these limitations, this is a high density map which is consistent with data collected by other authors using similar models and techniques (Worthington et al, 2016, Huang et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, recombination rates are known to differ between sexes in both plants and animals (Lorch, 2005). For example, Huang et al (2018) found that the male genetic map of Clementine mandarin was notably larger than its female counterpart. Another possible reason for the difference in the sizes of the linkage maps is that OTA-S was obtained by bulk seed harvest produced in isolation from four tetraploid (2 n = 40) clones derived from PI 299929 and from a cross between PI 299928 and PI 299929 (Voigt, 1976).…”
Section: Discussionmentioning
confidence: 99%
“… Bernet et al (2010) reported high collinearity between Fortune “mandarin” and Poncirus trifoliata . More recently, the availability of reference whole genome sequence allowed to compare genetic and physical maps and globally confirmed the good conservation of marker order between P. trifoliata and “Sunki” mandarin ( Curtolo et al, 2018 ) and P. trifoliata and sweet orange ( Huang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 89%